PENGARUH MEDIA LEAFLET TERHADAP PENGETAHUAN BAHAYA MEROKOK PADA REMAJA PEROKOK (Politeknik Kesehatan Kemenkes Bandung, 2021)
According to WHO (2008) smoking in the long run is a major cause of such deadly illnesses as heart attacks, cancer, and lung diseases. Indonesia ranks third with the world’s highest number of smokers. There are 20% smokers in Indonesia is in 13-15 years old. Youth in Holis RT 03 RW10 Bandung has a habit of smoking. According to the research of Indah R., Dewi P., and Maya F. (2019), showed the results that there was an influence between before and after given a medical education to the knowledge of dangers of smoking. There is a lot of media to be used to educate some of them. Husni A., Erdi I., and Atelia I. (2014) said that the results of media leaflet are more effective in building knowledge. The purpose of this study is to know the influence of leaflet media on the knowledge of the dangers of smoking in young smokers in the RT 03 RW 10 vilage of Warung Muncang Bandung City. The design of the study is used pre-exeriments with the design of one group pretest-posttest without control. The location of the this study is in RT 03 RW 10 Vilage of Warung Muncang Bandung City. The population in this study was 30 people who were taken entirely as samples of the study bye total sampling technique. The results show that the average score of respondent’s knowledge before given a leaflet is 72,33. The average score of respondent’s knowledge after being given a leaflet is 79,63. The percentage of knowledge increased is 10,09%. The p value on both before and after given a leaflet is (p=0,054).the conlusion is leaflet media doesn’t increase knowlage of smoking dangerous in young smokers in the RT 03 RW 10 Vilage of Warung Muncang Bandung City.